Moving beyond reaching women in seed systems development - Puskur, Ranjitha; Mudege, Netsayi N.; Njuguna-Mungai, Esther; Nchanji, Eileen Bogweh; Vernooy, Ronnie; Galiè, Alessandra; Najjar, Dina (International Food Policy Research Institute, 2021)
Seed is critical to food security as the first link in the food value chain (Galiè 2013) and can be a powerful agent of change (Reddy et al. 2007). Similarly, women’s empowerment and gender equality are key to food and nutrition security (Agarwal 2018). The interplay between the two is becoming increasingly important: socioeconomic and gender differences in seed and food security must be understood to target seed interventions effectively (FANRPAN 2011). However, the importance of seed systems to empower women has so far been neglected. This chapter contributes toward closing this gap. Gender analysis is important for a comprehensive understanding of seed systems and to shape effective and inclusive interventions that go beyond reaching women to benefit and empower them.